2002
DOI: 10.1161/hc0902.104706
|View full text |Cite
|
Sign up to set email alerts
|

Trunk Fat and Blood Pressure in Children Through Puberty

Abstract: Background-Fat distribution is well recognized as a cardiovascular risk factor in adults. The association between android fat distribution and cardiovascular risk factors, such as blood pressure (BP), was previously reported in an African-American and Caucasian pediatric population. The aim of the present study was to investigate the relationship between BP and body fat distribution in a large cross-sectional pediatric sample. The effects of race, sex, and puberty on this relationship were assessed. Methods an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
45
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 31 publications
10
45
0
1
Order By: Relevance
“…Consequently, for many with high BP levels, measures directed at the long-term prevention of cardiovascular morbidity may need to be started in adolescence to achieve maximal effectiveness. Even though BMI and all the adiposity indices were found to be significantly associated with BP levels in both sexes, BMI and body fat mass showed the strongest association, most closely related to SBP in both genders and to DBP only in males, in agreement with the literature data indicating that BMI contributes significantly to BP variability (19)(20)(21)24,27,46) , even in non-obese subjects (24,25) . The correlation between parental and adolescents' BMI values supports previous findings (18,(54)(55)(56) showing an influence of both parents' BMI on their children.…”
Section: Discussionsupporting
confidence: 89%
“…Consequently, for many with high BP levels, measures directed at the long-term prevention of cardiovascular morbidity may need to be started in adolescence to achieve maximal effectiveness. Even though BMI and all the adiposity indices were found to be significantly associated with BP levels in both sexes, BMI and body fat mass showed the strongest association, most closely related to SBP in both genders and to DBP only in males, in agreement with the literature data indicating that BMI contributes significantly to BP variability (19)(20)(21)24,27,46) , even in non-obese subjects (24,25) . The correlation between parental and adolescents' BMI values supports previous findings (18,(54)(55)(56) showing an influence of both parents' BMI on their children.…”
Section: Discussionsupporting
confidence: 89%
“…42,43 In children, gender differences in abdominal adiposity are closely linked to age-and puberty-related changes in fat distribution. 19,[44][45][46] In our study, we found significant differences in BMI between genders and ethnic groups, underlying important differences in total adiposity. As abdominal adiposity is highly influenced by total adiposity also in children, 45 we corrected VAT for SAT and BMI in order to minimize this effect.…”
Section: Discussionsupporting
confidence: 49%
“…[6][7][8][9][10] Since 1992, visceral adiposity has been evaluated by Magnetic Resonance Imaging (MRI) in children and it has been related to glucose metabolism, lipids abnormalities and hypertension. [11][12][13][14][15][16][17][18][19][20] However, direct measurements of visceral adipose tissue (VAT) cannot be proposed for field studies due to their cost and technical difficulties. 21 Several anthropometric indexes have been suggested as indexes of VAT.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the results of the present study are consistent with previous investigations of adiposity and BP in young children. [28][29][30][31][32][33] The results also provide further evidence that simple anthropometric indices such as the BMI, skinfolds, and WC are important and feasible measures to identify young children who may be at risk of subsequent obesity, hypertension, and CVD. To support the use of simple anthropometric indices in clinical settings, we have previously shown that the BMI and skinfold thickness are highly correlated with DXA measures of %BF, FFM, and FM in this sample.…”
Section: Discussionmentioning
confidence: 87%